Depression among refugee youth in an outpatient healthcare center—prevalence and associated factors - Schumacher, Lea; Echterhoff, Jette; Zindler, Areej; Barthel, Dana (Frontiers in Psychiatry, 2024)
Background: Due to armed conflict and other crises, many children worldwide have to flee their home country and are, consequently, at high risk for mental health problems.Objective: As the majority of previous research on refugee minors focused on posttraumatic stress disorder (PTSD), we aimed to assess the prevalence and risk factors for depression in a clinical sample of refugee youth.Methods: Data were collected during the standard diagnostic process in an outpatient refugee clinic in Germany. We assessed the prevalence of depression based on a diagnostic interview and investigated the association between age, gender, duration of flight, accompanying status, number of interpersonal traumatic experiences, residence status and PTSD diagnosis with a depression diagnosis. More specifically, we conducted a Bayesian logistic regression with these associated factors as predictors and the presence of depression as the outcome. Additionally, we conducted a Bayesian network analysis including all these variables.Results: The majority of the 575 included refugee children was male (n = 423, 73.6%) and on average 15.1 years old (SD = 2.69). Nearly half of the children (n = 243, 42.26%) met the diagnostic criteria for depression, of which most also showed a comorbid PTSD diagnosis. We found strong evidence that age, gender, number of traumatic experiences, and a diagnosis of PTSD were related to depression. The network analysis indicated that only age, gender and PTSD were directly associated to depression. Flight-related factors were only indirectly associated with depression due to their associations with number of traumatic experiences and PTSD diagnosis.The high prevalence of depression and its strong associations with PTSD suggest that refugee minors are likely to experience depressive symptoms which might develop from PTSD symptoms. This implies a need for monitoring depressive symptoms in refugee minors, especially when these have a PTSD diagnosis.